Hypertrophic Osteopathy Associated with Lung Adenocarcinoma in a Cat: An Overview - Janevski, Aleksandar; Dimitrievski, Boris; Murdzeva, Emilija; Bozhinovski, Dimitar; Nikolova, Biljana; Mitrov, Dine (Walter de Gruyter GmbH, 2023)
Abstract Hypertrophic osteopathy (HO) is a pathological condition characterized by progressive, bilateral and symmetrical periosteal bone hyperostosis. Hypertrophic osteopathy is considered a secondary disease that occurs as a consequence of many chronic processes, which are primarily localized in the thoracic cavity (intrathoracic lesions), and less as a result of changes in the abdominal cavity (extrathoracic lesions). We describe a case of a 3.5-year-old female unneutered short-haired cat with a history of chronic weight loss, decreased appetite, dyspnea, and wet cough. During the native X-ray examination of the thoracic cavity, a clearly limited homogeneous radiopaque shadow which covered the entire thoracic cavity was found, as well as periostitis of the front limbs, mainly on the humeri, radii and ulnae. After euthanizing the cat, a control X-ray examination and necropsy of the body was performed. The necropsy revealed a soft-tissue proliferation measuring 13 x 5 x 4 cm and weighing 228 g, and a pronounced ossified periostosis of the long bones, while the histopathological findings revealed adenocarcinoma of the lung with metastasis to the mediastinal lymph nodes. The outcome of hypertrophic osteopathy mostly depends on the primary cause. If the initial lesion had been identified and removed on time, the condition would have also receded spontaneously. The primary tool in determining hypertrophic osteopathy is X-ray diagnosis. Considering the determination of this condition is an indicator of ongoing severe disease, especially in the thoracic cavity, its early diagnosis would lead to prolongation of the animal's life.